1967
DOI: 10.1017/s002531540005640x
|View full text |Cite
|
Sign up to set email alerts
|

The growth of Haliotis tuberculata: results of tagging experiments in Guernsey 1963–65

Abstract: A tagging investigation on the ormer (Haliotis tuberculata L.) has been carried out for the Guernsey States Sea Fisheries Committee. Cementing plastic discs to the shell has proved a satisfactory technique since substantial numbers of 40—50% were recovered after 1 and 2 years in the open sea off the west coast of Guernsey. From the increase in shell size of the recovered specimens the mean growth rate has been shown to be about 15 mm of shell length per year up to a shell size of 50 mm, and thereafter decreasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
1

Year Published

1969
1969
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 5 publications
6
28
1
Order By: Relevance
“…Growth appears to be fastest during autumn at both localities, but the magnitude of the seasonal difference is greater at Peraki Bay. Seasonal differences in growth rate have been recorded for other haliotids (Cox 1962;Sakai 1962;Leighton & Boolootian 1963;Forster 1967;Newman 1968) and for 2 species the magnitude of the seasonal difference appears similar to that found for H. iris at Peraki Bay. Forster (1967) found that H. tuberculata grew about 70% of their annual increment in a single autumn month and Cox (1962) reported that almost the entire annual increment of H. rufescens was attained during the winter.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Growth appears to be fastest during autumn at both localities, but the magnitude of the seasonal difference is greater at Peraki Bay. Seasonal differences in growth rate have been recorded for other haliotids (Cox 1962;Sakai 1962;Leighton & Boolootian 1963;Forster 1967;Newman 1968) and for 2 species the magnitude of the seasonal difference appears similar to that found for H. iris at Peraki Bay. Forster (1967) found that H. tuberculata grew about 70% of their annual increment in a single autumn month and Cox (1962) reported that almost the entire annual increment of H. rufescens was attained during the winter.…”
Section: Discussionsupporting
confidence: 70%
“…Variability of growth parameters between localities has been demonstrated for many other haliotids (Leighton & Boolootian 1963;Forster 1967;Poore 1972a;Shepherd & Laws 1974). Shepherd & Laws (1974) reported that both H. ruber and H. laevigata grew faster in exposed areas than sheltered areas.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Decreased growth rate appears not just to be the result of general decline in metabolism among older animals, but rather to be at least partly due to the competitive demand of the gonad for energy. In support of this, a number of authors have reported decreased growth rates for abalone specifically during periods of gonad production (Shepherd and Heam, 1983;Keesing and Wells, 1989), and negligible growth during most of the year except for a growth spurt after spawning (Cox, 1962;Foster, 1967;Poore, 1972;Sainsbury, 1982;Keesing and Wells, 1989). The present study took place over 10 weeks from April to July, which corresponds to the time of gametogenesis and negligible somatic growth in H. hmtschatkuna (Paul et al, 1976).…”
Section: Discussionsupporting
confidence: 64%
“…This species has a distribution from the Azores in the west, the Mediterranean in the east, the West African coast in the south and the Channel Islands in the north. The ecology of H. tuberculata has been the subject of intense study (Forster 1962, 1967, Hayashi 1980a, Peck 1983, 1989, Peck et al 1987, Peck & Culley 1990, Mgaya & Mercer 1994. H. tuberculata is dioecious and sexes are easily distinguished by examining the large gonad visible from the underside of the shell (Hayashi 1980b).…”
Section: Introductionmentioning
confidence: 99%